Quarterly Pasidungog to Parents: An Intervention to Improve Parental Involvement in Printed Modular Instruction - Lugod, Vidala T. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Parental involvement in children’s education is crucial for their academic success. Active participation and collaboration between parents and schools can enhance children’s learning experiences and improve their academic performance. Thus, this action research focused on the effectiveness of quarterly Pasidungog as an intervention for parents to improve the academic performance of Grade 2 learners in Getafe 2 Central Elementary School, Getafe 2 District, Bohol Division. The researcher aimed to improve the academic performance of twelve (12) Grade II–2 learners. The twelve (12) learners, or 55% of the class, showed deficient academic performance. The monitoring checklist form was used as a data-gathering tool. Descriptive statistics such as frequency, percentage, and weighted mean were used for data analysis. Results showed that the learners’ academic performance improved after the Quarterly Pasidungog to parents, as shown in the mean difference before and after applying the intervention. It implies that the conduct of Pasidungog toward parents motivated them to perform their roles as para-teachers to their learners. Recommendations were proposed to encourage parental involvement and strengthen home-school collaboration.